Analisis Semiotika Representasi Kepedulian Sosial dalam Film a Man Called Otto - IzzulHaq, Muhammad Faris; Suparto, Diryo; Florina, Ike Desi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the representation of social care in the film A Man Called Otto through a semiotic approach of Charles Sanders Pierce. The object of this research is the film A Man Called Otto, with the aim of identifying and interpreting the signs, symbols, and meanings contained within it related to the representation of social care. The research method used is semiotic analysis, which involves identifying iconic, indexical, and symbolic signs in the film, as well as interpreting meanings based on cultural and social contexts. The results of the study show that the film A Man Called Otto represents social care in various ways, including through the main character's actions in helping neighbors, interactions between diverse characters, and the transformation of Otto's character from an indifferent individual to a more caring one.